Broadband Achromatic and Polarization Insensitive Focused Optical Vortex Generator Based on Metasurface Consisting of Anisotropic Nanostructures - Song, Naitao; Xu, Nianxi; Gao, Jinsong; Jiang, Xiaonan; Shan, Dongzhi; Tang, Yang; Sun, Qiao; Liu, Hai; Chen, Xin (Frontiers in Physics, 2022)
Optical vortex (OV) beams are ideal carriers for high-capacity optical communication, and long-wave infrared (LWIR) is the ideal wavelength band for long-range optical communication. Here, we propose a method for the achromatic generation of focused optical vortex (FOV) beams with arbitrary homogenous polarization states in the LWIR using a single all-germanium metasurface. The chromatic aberration and polarization sensitivity are eliminated by superimposing a polarization-insensitive geometric phase and a dispersion-engineered dynamic phase. The method is validated using two broadband FOV generators with the same diameter and focal length but different topological charges. The results indicate that the FOV generators are broadband achromatic and polarization insensitive. The proposed method may pave the way for chip-scale optical communication devices.